The highs and lows of beta activity in cortico-basal ganglia loops - Brittain, J; Sharott, A; Brown, P (Blackwell Publishing Ltd, 2014)
Oscillatory activity in the beta (13-30 Hz) frequency band is widespread in cortico-basal ganglia circuits, and becomes prominent in Parkinson's disease (PD). Here we develop the hypothesis that the degree of synchronization in this frequency band is a critical factor in gating computation across a population of neurons, with increases in beta band synchrony entailing a loss of information-coding space and hence computational capacity. Task and context drive this dynamic gating, so that for each state there will be an optimal level of network synchrony, and levels lower or higher than this will impair behavioural performance. Thus, both the pathological exaggeration of synchrony, as observed in PD, and the ability of interventions like deep brain stimulation (DBS) to excessively suppress synchrony can potentially lead to impairments in behavioural performance. Indeed, under physiological conditions, the manipulation of computational capacity by beta activity may itself present a mechanism of action selection and maintenance. © 2014 The Authors. European Journal of Neuroscience published by Federation of European Neuroscience Societies and John Wiley and Sons Ltd.